Model to increase profitability and customer satisfaction client in a veterinary clinic in Peru, in the Post COVID-19, using Lean Service methodologies, SCRUM and Digital Transformation. (LACCEI, 2024)
Veterinary or Veterinary Clinics have gone increasing over the years in Peru, forming in the city ​​of Lima 474 pet stores and 640 veterinarians which They offer their services around 1.7 million households. The growing trend of having pets is being driven by millennials and centennials, who prefer to have pets instead of children, causing a trend not only in Peru but also In the world, among the main pets are cats and dogs. However, due to changes in habits generated due to the COVID-19 pandemic and the use of technology in all aspects of life of the group of people described has generated a change in the habits of use of this type of clinics, where the demand for service has grown. It also presents various problems mainly in customer service, where the main complaints are in a long period of time waiting to be served, non-standardized processes in the pet care, lack of stock of products, information deficient clinical history, among others. For this reason, the The main objective of this research is to increase the efficiency of the customer service process through Lean Service, SCRUM and Digital Transformation